Business Process Management Employee Recruitment PT. EXA Solutions Partners - Setyananda*, Andre Firza; Putri, Anggi Yuniar; Alijoyo, Franciskus Antonius (Riwayat: Educational Journal of History and Humanities, 2023)
Since 2004, PT EXA Mitra Solusi (EXA) has been an industrial company that provides outsourcing services or Business Process Outsourcing (BPO) in the areas of recruitment services, marketing sales outsourcing, operations outsourcing, customer service and training for HR training and development. As an outsourcing company, PT EXA Mitra Solusi provides business solutions that follow and adapt to current business needs, from workforce requirements to system management and monitoring employee performance. As well as helping businesses to grow perfectly. Because many prospective employees are applying to this company, this research is needed by the company for time efficiency and employee effectiveness in the employee recruitment process. The benefit of this research is that it is hoped that each company will get quality employees as needed by the company for the company's development.